Computational Studies of Rhubarb’s Anthraquinone Glycosides as Anti-Diabetic Drug Candidates through Sodium-Glucose Cotransporter-2 Inhibition - Putra, Wira Eka; Sustiprijatno; Hidayatullah, Arief; Widiastuti, Diana; Heikal, Muhammad Fikri (Iraqi Journal of Science, 2024)
Type 2 diabetes mellitus continues to pose a significant global health concern, warranting increased attention. This metabolic disorder is influenced by various factors, such as lifestyle, diet, environment, and genetics. While several approaches have been developed to address the incidence of type 2 diabetes mellitus, current treatments remain inadequate and necessitate further improvement. In this study, our objective was to assess the potential antidiabetic efficacy of anthraquinone glycosides present in rhubarb (specifically physcion diglucoside and aloe-emodin-8-glucoside) as potential inhibitors of the sodium-glucose cotransporter-2. We employed an in silico study to evaluate their inhibitory properties. The computational prediction was performed included the target protein, ligands retrieval, and preparation. Furthermore, the molecular docking process was conducted to assess the interaction between the target protein and ligands. Subsequently, data visualization and analysis were performed. Various indicators were evaluated, including the characteristics of the target molecule and drug candidates, binding affinity scores, interaction positions, types of chemical interactions, amino acid residues involved, hydrophobicity, formation of hydrogen bonds, interpolated charge, and ionizability. These comprehensive evaluations provided valuable insights into the molecular interactions and potential efficacy of the tested compounds. In this computational study, we demonstrated that the both rhubarb anthraquinones, physcion diglucoside and aloe-emodin-8-glucoside, have a great potential as antidiabetic agent by inhibiting the action of the sodium-glucose cotransporter-2. Thus, the inactive the sodium-glucose cotransporter-2 can prevent the excessive number of glucose plasma level in type two diabetes mellitus people.